2023
DOI: 10.1155/2023/5134332
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Activity of Ginger (Zingiber officinale) Extracts In Vitro and Food Model

Abstract: The present study aims at investigating the antibiofilm activity of two various ginger (Zingiber officinale) extracts in comparison to peracetic acid in broth culture and food model against pathogenic bacteria. The GC-MS analysis proved that the major components in the subcritical water extract of ginger were Zingerone (28.99%) and cis-6-shogaol (22.1%), while in the aqueous-ethanolic extract was Gingerol (28.404%) and Zingiberene (11.954%). According to the results, ginger subcritical water extract in a conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…10 g of the dry powder of ginger was mixed with 100 ml of distill water with mixed by an electrical mixer for half an hour, then the mixture was filtered using layers of medical gauze and rounded 3000 cycles during 10 minutes in centrifuge, then filtered using filter paper to get rid of impurities. The extract dried in the oven at 40 °C and then kept in the refrigerator until use [9].…”
Section: Methodsmentioning
confidence: 99%
“…10 g of the dry powder of ginger was mixed with 100 ml of distill water with mixed by an electrical mixer for half an hour, then the mixture was filtered using layers of medical gauze and rounded 3000 cycles during 10 minutes in centrifuge, then filtered using filter paper to get rid of impurities. The extract dried in the oven at 40 °C and then kept in the refrigerator until use [9].…”
Section: Methodsmentioning
confidence: 99%
“…Akbari [ 14 ] investigated the activity of antibiofilms against pathogenic bacteria through subcritical water and aqueous-ethanolic extracts of ginger in broth cultures and food model agents. The results showed that 50% ( v/v ) ginger subcritical water extract had the highest antibiofilm activity, similar to 0.5% peracetic acid (control).…”
Section: Antibacterial and Antioxidant Properties Of Natural Extractsmentioning
confidence: 99%